New pathway for the preparation of pyrochlore Nd2Zr2O7 nanoparticles. Issue 6 (July 2015) - Kong, Linggen; Karatchevtseva, Inna; Aughterson, Robert D.; Davis, Joel; Zhang, Yingjie; Lumpkin, Gregory R.; Triani, Gerry
Abstract: Pyrochlore Nd2 Zr2 O7 nanoparticles were prepared by complex-precipitation in aqueous media, followed by calcination in MgO matrix and subsequent dissolution processing. A suite of characterization techniques, including X-ray diffraction, Raman, TEM, SEM, dynamic light scattering, and nitrogen sorption, was employed to investigate the structure and particle size of the synthesized nano materials. Results show that calcination at 1200 °C for 20 h forms Nd2 Zr2 O7 with pyrochlore structure. The matrix phase (MgO) had no effect on the formation of pyrochlore phase. The MgO phase was readily removed by dissolution at 0.5 M HNO3 aqueous solution; and the remaining pyrochlore Nd2 Zr2 O7 nanoparticles had a diameter of approximately 200 nm estimated by TEM and approximately 550 nm determined by light scattering due to slight aggregation. The bulk density of the pelletized powder reached approximately 99% of theoretical value, after uniaxial pressing at 2.0–2.5 MPa and sintering at 1400 °C for 48 h.